Fractal Modeling of Retinal Blood Vessel System - Deviha, V. Shanthoshini; RENGARAJAN, P.; Jahir Hussain, Dr. R. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper proposes a novel approach to extract the main features of retinal blood vessel system. The purpose of the study is to evaluate the blood flow in the retinal blood vessel system using Darcys law, Reynolds number, Poiseuilles law and Forchheimer equation. A new algorithm has been established to traverse through the retinal blood vessel system in a robust manner.